(untitled) (Sebha University Conference Proceedings, 2024)
Applying the exploratory stage to academic publication data allows us to uncover valuable insights from unstructured data, aiding Sebha University administrators in enhancing academic scientific output. One major issue in research production is the lack of citations, which academics are keen to understand. They seek to identify key factors that can help them publish in journals where their work will be cited. Additionally, evaluation committees and efforts to improve the quality of educational institutions require structured knowledge and organized data, rather than raw, hard-to-analyze information. By utilizing the exploratory stage, we were able to identify the most active years of scientific publishing and the journals whose research receives few citations.